(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
Gold prices have been on the increase since 1793, even though the US dollar still holds the leading position. The economic and financial crises that have hit the global economy have continually strengthened the position of gold as a safe haven, keeping it intact and intact even in the face of financial and economic instabilities. In the 2008 subprime mortgage crisis that is still affecting the world economy, gold peaked in September 2011 with its highest price of 1920 per ounce in history. This peak was also affected by the sovereign debt crises in the European Union. Gold has recently become in high demand again by investors as well as central banks especially in Europe, but there is also a growing demand by the emerging markets in an effort to diversify against the unstable dollar. This, combined with changes in the US dollar over the euro and more intense movements in the global gold markets have created significant interest amongst researchers. The causal relationship between the exchange rate of the US dollar and the price of gold has been studied in many economic studies with inconclusive findings. Based on the assumption of causal relationships between the dollar value against other currencies to global gold prices in the period of 1999-2010, the study questions: To what extent do fluctuations in the US dollar affect international gold prices? This study aims to investigate the nature of the dollar’s impact on global gold prices through both theoretical and empirical approaches, utilizing the EViews software for econometric analysis.